Vertical Distributions of Soil Nutrients and Their Stoichiometric Ratios as Affected by Long Term Grazing and Enclosing in a Semi-Arid Grassland of Inner Mongolia - Juan Hu; Daowei Zhou; Qiang Li; Qicun Wang (Agriculture, 2020)
Grazing and enclosing are two of the most important grassland managements. In order to evaluate the effects of different managements on the ecosystem balance of grassland, the vertical distributions of soil nutrients and their stoichiometric ratios were determined in the plots of grazing and enclosing over 38 years in a semi-arid grassland of Inner Mongolia. The results showed that total nitrogen (TN), total phosphorus (TP), available nitrogen (AN), calcium (Ca), magnesium (Mg) and sulfur (S) contents in 0–100 cm soil in the long term enclosing plot were lower than the long term grazing plot and these changes were much greater in the surface soil than in deep soil. However, the soil organic carbon (SOC) and available phosphorus (AP) contents in the long term enclosing plot in the surface soil were higher (p < 0.01) compared with the long term grazing plot. In addition, long term enclosing increased the C/N ratio in each soil layer and improved C/K and C/P ratios in the surface soil compared with long term grazing. However, significant decreases of N/P and N/K ratios in the long term enclosing plot in each soil layer were observed. In conclusion, enclosing for 38 years decreased most of nutrients and reduced the nutrients’ mineralization in the surface soil especially and thus might restrict nutrients cycling in a semi-arid grassland of Inner Mongolia.